Type 2 diabetes in the Sultanate of Oman. - Al-Shookri, A.; Khor, Geok Lin; Chan, Yoke Mun; Loke, Seng Cheong; Al-Maskari, M. (Nutrition Society of Malaysia, 2011)
During the past four decades, Oman has undergone a rapid socioe-conomic and epidemiological transition leading to a substantial reduction in the prevalence of various communicable diseases, including vaccine-preventable diseases. Health care planning together with the commitment of policy makers has been a critical factor in this reduction. However, with rapid social and economic growth, lifestyle-related non communicable diseases have emerged as new health challenges to the country. Diabetes and obesity are leading risks posed by the chronic diseases. The burden of diabetes has increased sharply in Oman over the last decade, rising from 8.3% in 1991 to 11.6% in 2000 among adults aged 20 years and older. The World Health Organization (WHO) predicted an increase of 190% in the number of subjects living with diabetes in Oman over the next 20 years, rising from 75,000 in 2000 to 217,000 in 2025. There is a lack of awareness of the major risk factors for diabetes mellitus in the Omani population generally. As education is often the most significant predictor of knowledge regarding risk factors, complications and the prevention of diabetes, health promotion in Oman is deemed critical, along with other prevention and control measures. Suitable prevention strategies for reducing the prevalence of diabetes in Oman are discussed. Recommendations are made for reforms in the current health care system; otherwise, diabetes will constitute a major drain on Oman's human and financial resources, threatening the advances in health and longevity achieved over the past decades.